COLOR GAME OF ONDEL-ONDEL AS CULTURAL EDUCATION MEDIA FOR CHILDREN - Wahidiyat, Mita Purbasari; Tabroni, Imam (Capture : Jurnal Seni Media Rekam, 2020)
Educational games are a play-while-learning approach for children today, especially in big cities like Jakarta. As an icon of Jakarta, Ondel-Ondel can be found in various corners of Jakarta daily. His familiar figure makes it a suitable subject for learning to color while getting to know about the Betawi culture for children. The Ondel-Ondel coloring application is a multimedia-based educational game designed for children aged 3-7 years, in which information about the elements that make up the attributes of Ondel-Ondel can be inserted. This study combines the educational game implementation method with a user-centered approach, where this method connects the let's draw game with a brief knowledge of Ondel-Ondel as a traditional Betawi art. Analysis of Ondel-Ondel supporting elements or attributes uses Morris Semiotics which focuses on syntax, semantics, and pragmatics by categorizing form, content, and context. This game helps children to get a lot of information about Ondel-Ondel and stimulate their imagination.